Institutional Design for Financial Market - WÓJCIK-CZERNIAWSKA Agnieszka; MARECKI Krzysztof (Communications of International Proceedings, 2022)
Around the world countries are keen to develop their economic system to maintain stability of their economy stability, reliability of public and upholding the competence to fulfil the needs of the users and also to raise the development in actual economy. This article comprises regulatory institutional models that are in process and are in exercise in specific authorities, the public oddity of regulation and the part of self-regulation and the role of the central bank in financial regulation of financial markets. In order to maintain the financial self-sufficiency a close inspection by auditors and suitable reforms in legislators is vital.
Keywords: Institutions; Executive tribunal; financial stability; pre-crisis; Eurozone